(x-2)(4x+5)=9

Simple and best practice solution for (x-2)(4x+5)=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-2)(4x+5)=9 equation:


Simplifying
(x + -2)(4x + 5) = 9

Reorder the terms:
(-2 + x)(4x + 5) = 9

Reorder the terms:
(-2 + x)(5 + 4x) = 9

Multiply (-2 + x) * (5 + 4x)
(-2(5 + 4x) + x(5 + 4x)) = 9
((5 * -2 + 4x * -2) + x(5 + 4x)) = 9
((-10 + -8x) + x(5 + 4x)) = 9
(-10 + -8x + (5 * x + 4x * x)) = 9
(-10 + -8x + (5x + 4x2)) = 9

Combine like terms: -8x + 5x = -3x
(-10 + -3x + 4x2) = 9

Solving
-10 + -3x + 4x2 = 9

Solving for variable 'x'.

Reorder the terms:
-10 + -9 + -3x + 4x2 = 9 + -9

Combine like terms: -10 + -9 = -19
-19 + -3x + 4x2 = 9 + -9

Combine like terms: 9 + -9 = 0
-19 + -3x + 4x2 = 0

Begin completing the square.  Divide all terms by
4 the coefficient of the squared term: 

Divide each side by '4'.
-4.75 + -0.75x + x2 = 0

Move the constant term to the right:

Add '4.75' to each side of the equation.
-4.75 + -0.75x + 4.75 + x2 = 0 + 4.75

Reorder the terms:
-4.75 + 4.75 + -0.75x + x2 = 0 + 4.75

Combine like terms: -4.75 + 4.75 = 0.00
0.00 + -0.75x + x2 = 0 + 4.75
-0.75x + x2 = 0 + 4.75

Combine like terms: 0 + 4.75 = 4.75
-0.75x + x2 = 4.75

The x term is -0.75x.  Take half its coefficient (-0.375).
Square it (0.140625) and add it to both sides.

Add '0.140625' to each side of the equation.
-0.75x + 0.140625 + x2 = 4.75 + 0.140625

Reorder the terms:
0.140625 + -0.75x + x2 = 4.75 + 0.140625

Combine like terms: 4.75 + 0.140625 = 4.890625
0.140625 + -0.75x + x2 = 4.890625

Factor a perfect square on the left side:
(x + -0.375)(x + -0.375) = 4.890625

Calculate the square root of the right side: 2.211475752

Break this problem into two subproblems by setting 
(x + -0.375) equal to 2.211475752 and -2.211475752.

Subproblem 1

x + -0.375 = 2.211475752 Simplifying x + -0.375 = 2.211475752 Reorder the terms: -0.375 + x = 2.211475752 Solving -0.375 + x = 2.211475752 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.375' to each side of the equation. -0.375 + 0.375 + x = 2.211475752 + 0.375 Combine like terms: -0.375 + 0.375 = 0.000 0.000 + x = 2.211475752 + 0.375 x = 2.211475752 + 0.375 Combine like terms: 2.211475752 + 0.375 = 2.586475752 x = 2.586475752 Simplifying x = 2.586475752

Subproblem 2

x + -0.375 = -2.211475752 Simplifying x + -0.375 = -2.211475752 Reorder the terms: -0.375 + x = -2.211475752 Solving -0.375 + x = -2.211475752 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.375' to each side of the equation. -0.375 + 0.375 + x = -2.211475752 + 0.375 Combine like terms: -0.375 + 0.375 = 0.000 0.000 + x = -2.211475752 + 0.375 x = -2.211475752 + 0.375 Combine like terms: -2.211475752 + 0.375 = -1.836475752 x = -1.836475752 Simplifying x = -1.836475752

Solution

The solution to the problem is based on the solutions from the subproblems. x = {2.586475752, -1.836475752}

See similar equations:

| 45-15=-10m | | 2ln(x-7)=4 | | 4x+30=12x-15 | | 13-9x=198-44x | | 4k^2-9k-5=0 | | 2(4x-1)=22 | | 11x-31=7x+4 | | y-1/y-3=(y-1/y+5)+1 | | 17/3x+3/5=8/3x | | X^1/3-2=0 | | 2x^4-2=160 | | 6x-13=3(2x+9) | | y=-4/x+3 | | 8t-26=-30 | | 21/25=x/75 | | 7y=2+5x | | 2v+26=6v+30 | | 4(3y-2)+2(3y-2)= | | (u-2)(4+4)= | | 13=0-45x+9 | | -34-2x=11-7 | | 5/11=v/10 | | 5/11=v10 | | 87x-6x=8x+17 | | 87x-6x=8x | | y-(-4)=(-8/9)(x-8) | | 3(4a-7)=5 | | (-7u^2+8u+7)-(2u^2-9u-5)+(-7u^2+5u-7)= | | y-(-2)=(-3/4)(x-5) | | 2x-2=12-52 | | y-(-2)=(3/4)(x-5) | | 25b+20b^3= |

Equations solver categories